Effects of Different Organic Substrates on Quality of Vermicompost - Kumar, Dipak; Thakur, Manish; Babita (International Journal of Bio-resource and Stress Management, 2015)
The investigation was planned to work out the effect of various sources of organic matter such as animal dung, food waste, kitchen wastes, saw dust, parthenium, lantana, baggas, pine needle etc. on the quality of vermicompost. The organic carbon content in the vermicompost was decreased at greater extent at lower carbon: nitrogen ratio (30:1) compared to higher one. Other properties of vermicompost like nitrogen, organic carbon, ammonical nitrogen and nitrate nitrogen contents were also significantly higher in lower C:N ratio. The nutrient contents viz., Nitrogen, Phosphorus, Potassium, Calcium, Magnesium and Sulphur were found significantly higher under lower carbon nitrogen ratio of vermicompost. Use of pine needle as substrate was found inferior compared to all other substrates, whereas, boiled pine needle proved to be better option for vermicomposting. The quality of vermicompost prepared from Parthenium in combination with cow dung, baggas and kitchen waste was best compared to all other treatments. The use of boiled pine needle as substrate was found better compare to un-boiled one for better quality. Substrates of higher carbon: nitrogen ratio produced poor quality of vermicompost and also takes more time for decomposition, however, carbon: nitrogen ratio of 30 to 40 was found optimum for the process of vermicomposting.